Analisis Semantik dalam Lirik Lagu Hubb Wa Hayah Karya Baraa Masoud - Azizah, Fina Nur; Maulida, Ameisha Wahidatul; Hidayah, Nurul (LPPM Universitas KH.A. Wahab Hasbullah, 2023)
The song is one of the types of literary works, the song is a poem that has the meaning that the author wants to describe. The lyrics of the song hubb wa hayah tell about the real religion of Islam, not what has been underestimated so far. The purpose of this study is to describe the use of letter sentences in the lyrics of the song hubb wa hayah. The method used in conducting this analysis is a qualitative descriptive method. The data collection technique used is to observe with note-taking techniques, in order to obtain relevant data. The results of this study are that the author uses 32 letters in this song, there are also letters that do not have meaning according to the meaning of lafadz, but have different meanings.